Chapter Texto e paratextos à volta da viagem de Fernão de Magalhães: Maximilianus Transilvanus - István, Rákóczi (Studi e saggi, 2021)
Maximilianus Transilvanus's letter, De Moluccis insulis is one of the most important historical sources on the Magellanes-Elcano expedition, born immediately after the circumnavigation of the Earth by Victória. The crew of the ship was interviewed by Maximilianus Transilvanus shortly after the docking in the port of Seville in September 1522. This interview became the basis of the letter written in Latin and sent from the royal secretary to the archbishop of Salzburg, Lang, who had already been his benefactor. The letter is the first step of the transformation of these news into information. This study does not wish to analise the text, but rather the 'paratexts' of the letter: a piece of sagu palm broad, a paradisea bird and spieces attached to the letter.